Determination of an impact of the composition on the pH level and the concentration of ammonium nitrogen in soil of Pustomyty distrаct, Lviv region - Кanda, Maria; Malovanyy, Myroslav; Оdnorih, Zoryana (Publishing House of Lviv Polytechnic National University, 2017)
This research involves studying the application of palygorskite from Dashukivka Deposit and clinoptilolite from Sokyrnytsia Deposit in production of organic fertilizers prolonged. It is found that maximum ammonia sorption capacity is 1.56×10-2 mg-eq/g of sorbents. The composition proposed has a positive impact on condition of the studied soils. The pH level of soil solution shifts toward neutral, and the level of ammonium nitrogen is uniform throughout 24 days.
Keywords: ammonia; poultry manure; palygorskite; clinoptilolite; adsorption